La Antinomia Normativa entre el Art. 34 y 108 de la Ley de Minería, respecto del Tiempo para el pago de la Patente de Conservación, Genera Inseguridad Jurídica. - Vaca Valdiviezo, Miguel Andrés (2016)
This research study aims the legal recognition that there is a policy conflict between Article 34 and 108 of the Mining Act and the application of Article 34 ibí dem by the administrative authority "Industry Ministry" violates the right to safety legal, the right to due process, falling into a blindness sthatlimit the right to work and terminated with patrimonial benefits forth estate, who setaxesenrichthenationalheritage. Theproblemisgeneratedwithinthat has theminingconcessionaire to payforpatents, becauseononehand, Art. 34 of theMiningActprovidesthatthepayment of thepatentmust be madeuntilMarch of eachyear, in any case orforadministrativeor judicial extensionforthepayment of thispatentisgranted, and ontheotherhand Art. 108 of theMiningActexpresslyprovidesforanextensionforpayment of thepatent, to orderthe Sector Ministryshouldprovidewithin 60 days a miningconcession, to remedythebreach of anyoutstandingobligation of compliance (example: ifyoudidnotpaypatents to time couldpaywithin 60 daysgivestheabove standard) and thusriddingwasextinguisheditsmininglaw. Developmentwork in themostthoroughstudy of thatprovisionismade, as well as constitutionalprovisions and lawscompared, so indeedunderstandtheirintent and theirconsequences. Fromtheresultspossiblealternatives are presented, in orderthat more in line withthecurrent legal thatisgoingthroughour country measures are taken, as 5 theconstitutionalparadigmestablished and acceptedby Ecuador since 2008, isguarantor of Rights, and therefore favorable people. Hencepart of thisresearch, therecognitionthatrights are violatedwiththis legal precept, forfurtherachieveharmonization of it, ie, achievepartialreform of article 34 of theMiningLaw, in order to avoidmisinterpretations, withrespect to time to meetthepayment of patentminingconservation.